Imidazolium-grafted graphene oxide via free radical polymerization: An efficient and simple method for an interpenetrating polymer network as electrolyte membrane. (18th August 2018) - Ouadah, Amina; Luo, Tianwei; Wang, Jing; Gao, Shuitao; Wang, Xing; Zhang, Xin; Fang, Zhou; Wu, Zeyu; Wang, Jie; Zhu, Changjin
Abstract: In this work, graphene oxide (GO) is modified via free radical polymerization with butylvinylimidazolium (b-VIB) to produce GO/IM, which is characterized using FTIR spectral analysis, X-ray diffraction (XRD), thermogravimetric analysis (TGA), Raman analysis, X-ray photoelectron spectroscopy (XPS), elemental analysis, and a morphology study with transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Further, GO/IM is incorporated for an in-situ polymerization, with the synthesized copolymer para -methyl styrene/butylvinylimidazolium (PMS/b-VIB) and synthesized poly(4, 4′-diphenyl ether-5, 5′-bibenzimidazole) (DPEBI) as a matrix, giving nanocomposite membranes referred to as GO/IM-X. These nanohybrid membranes possess higher conductivity than the pristine membrane of PMS/b-VIB/DPEBI and the conductivity increases with increasing amount of GO/IM, reaching 78.5 mS cm −1 at 100 °C and 26.5 mS cm −1 25 °C (chloride conductivity), enhancements of about 14.93% and 33.16% compared to the pristine membrane. Nanocomposite membrane properties were investigated; the swelling ratio and water uptake, ion exchange capacity (IEC), thermal properties via TGA, structure characterization using FTIR, morphology via TEM and mechanical properties. Taken together, these results suggest the present nanohybrid membranes have great potential for use as polymer electrolyte membranes with fuel cell applications. Graphical abstract: Image 1